2022
DOI: 10.1111/1759-7714.14765
|View full text |Cite
|
Sign up to set email alerts
|

Diverse gut microbiota pattern between mild and severe cancer‐related fatigue in lung cancer patients treated with first‐line chemotherapy: A pilot study

Abstract: Background Cancer survivors perceive cancer‐related fatigue (CRF) as one of the most common symptoms. However, the potential relationship between CRF and gut microbiota has not been elucidated. Our study aimed to preliminary explore the diverse gut microbiota composition between mild and severe CRF in advanced lung cancer patients undergoing first‐line chemotherapy. Methods A total of 20 advanced lung patients treated with first‐line chemotherapy were enrolled, 10 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Of the two remaining studies, Deleemans and colleagues investigated fatigue following predominantly CT for mixed cancers and observed no association between fatigue and alpha diversity or composition [52]. Finally, Wei and colleagues compared mild and severe fatigue in 20 participants with advanced lung cancer, and similar to some previous studies, reported no difference in alpha or beta diversity, but various changes in composition between the two groups [58]. Specifically, in patients with mild fatigue, there were lower levels of Enterobacteriaceae family and Escherichia-Shigella genus, both known to lead to increased inflammation, and higher levels of Lachnospiracea, known to increase SCFA production.…”
Section: Fatigue Following Cancer Treatmentsmentioning
confidence: 81%
See 1 more Smart Citation
“…Of the two remaining studies, Deleemans and colleagues investigated fatigue following predominantly CT for mixed cancers and observed no association between fatigue and alpha diversity or composition [52]. Finally, Wei and colleagues compared mild and severe fatigue in 20 participants with advanced lung cancer, and similar to some previous studies, reported no difference in alpha or beta diversity, but various changes in composition between the two groups [58]. Specifically, in patients with mild fatigue, there were lower levels of Enterobacteriaceae family and Escherichia-Shigella genus, both known to lead to increased inflammation, and higher levels of Lachnospiracea, known to increase SCFA production.…”
Section: Fatigue Following Cancer Treatmentsmentioning
confidence: 81%
“…Of these studies that examined the influence of the gut microbiome on cancer treatmentrelated fatigue, all reported some differences in microbial composition between the participants with and without fatigue [18,31,52,[56][57][58]. The first of these was a study in 12 breast cancer survivors that reported fatigue being associated with higher alpha and beta diversity [31].…”
Section: Fatigue Following Cancer Treatmentsmentioning
confidence: 99%
“…The biology of fatigue is complex, and a variety of mechanisms have been implicated in its etiology and persistence, including dysregulation in key neurotransmitter and neuroendocrine systems, cellular metabolism, and immune and inflammatory activities, with emerging evidence in the gut microbiome. [184][185][186][187] Many of these processes are potential targets for intervention, and agents that influence these processes are currently under investigation (eg, bupropion 155 ; probiotic supplementation 188 ). With continuous advances in our understanding of the biology of CRF, there are exciting opportunities for developing and testing targeted pharmacotherapies to help manage this symptom.…”
Section: Discussionmentioning
confidence: 99%
“…92 Lachnospiraceae UCG-008 is likely a butyrate producer, since the Lachnospiraceae family is known to contain many butyrate-producing members. [91][92][93][94] There is discrepancy between different studies as to whether Lachnospiraceae members are increased or decreased in various intestinal perturbations, and whether this is beneficial or detrimental to the host. 91,[94][95][96][97][98][99] It has been suggested that the impact of Lachnospiraceae members on the host is likely species or strain specific.…”
Section: At Least One Other Dss Colitis Study Has Seen the Growth Pat...mentioning
confidence: 99%